A sustainable approach to hierarchically porous carbons from tannic acid and their utilization in supercapacitive energy storage systems. Issue 23 (31st May 2019) - Díez, Noel; Ferrero, Guillermo A.; Sevilla, Marta; Fuertes, Antonio B.
Abstract : We synthesized hierarchically porous carbons with a high surface area using a salt template-assisted chemical activation approach using tannic acid as the precursor. When tested as electrode active materials for supercapacitors, they exhibit a high capacitance in aqueous and organic electrolytes at high current rates. Abstract : Hierarchically porous carbons with a high surface area have been synthesized by a salt template-assisted chemical activation approach using a biomass-derivative, tannic acid, as the carbon precursor. Tannic acid is pyrolyzed in the presence of KCl, acting as the template and reaction medium, and K2 CO3, serving as both the template and activating agent. An important characteristic of our synthesis strategy is that the carbonaceous matter is immersed in a melted mixture constituted by the activating agent and KCl. This reaction medium greatly favours reactivity between the carbon and K2 CO3, and yet enhances the carbon yields, which are in the 32–38% range. The porous carbons have large specific surface areas, in the 2250–2750 m 2 g −1 range, and their microporosity can be fine-tuned by adjusting the carbonization temperature. When these carbons are tested as the electrode active material for supercapacitors, they exhibit a high capacitance in aqueous and organic electrolytes. The short diffusion pathways provided by their hierarchical architecture allow an excellent electrochemical response in situations of high power demand.